Visual rhetoric based on triadic approach: Intellectual knowledge, visual representation and aesthetics as modality - Koksal, Fatma Nazli; Inatci, Umit (Walter De Gruyter Gmbh, 2020)
The aim of the present study is to evaluate Sonja Foss's Rhetorical Schema for the Evaluation of Visual Imagery (1994) as well as reflect upon several points for further consideration; and finally suggest a renewed triadic approach as a method for analyzing art-relevant visual imagery. The triadic approach to be discussed assumes three correlative layers: the intellectual knowledge, function of the artistic content as the visual representational component, and aesthetics as modality. This study will include the analysis of a print advertisement that used an artwork as its content of visual rhetoric, and this will inform further discussions on the proposed approach. The contribution of this renewed triadic approached to the field of visual rhetoric has the advantage of expanding and possibly improving rhetorical analysis methods of visual imagery.
Keywords: visual rhetoric; visual representation; aesthetics; artwork; advertising